Triangle Training and Diamond Exercise on Passing Skills in Futsal Extra-Curricular Students at High School - Iffat Umar Madao; Sahabuddin Sahabuddin; M. Adam Mappaompo (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Passing accuracy is a crucial element in futsal, yet extracurricular students often fail to reach optimal skill levels due to limited variations in training methods. This study aims to evaluate: (1) the effect of triangle training on passing skills; (2) the effect of diamond training on passing skills; and (3) the difference in effectiveness between triangle and diamond training among futsal extracurricular students at High School 1, Toraja Utara. Methods: This quasi-experimental study employed a two-group pretest-posttest design. A total of 40 students were selected through total sampling and divided into two groups using the ordinal pairing technique. Data were collected via pretest, treatment, and posttest using a futsal passing skills test and analyzed using an independent sample t-test at a 0.05 significance level. The analysis revealed that both methods significantly improved technical skills (p = 0.001 < 0.05). However, the triangle training group recorded a more substantial average increase, from 4.50 to 9.30, compared to the diamond training group, which increased from 4.45 to 6.80. Triangle training is significantly more effective than diamond training in improving passing skills. This superiority is attributed to the dynamic and adaptive variations in angles, distances, and ball trajectories inherent in the triangle pattern, which more effectively hone students' accuracy and ball control. These findings provide a practical contribution for coaches in implementing more efficient training models for beginner futsal players.